Perhitungan Kestabilan Lereng Di Dusun Waehakila (Warasia), Kecamatan Sirimau, Kota Ambon - Wahyu A. Wardhana,; Sjafrudin Latar; Apri A. Matitaputty (General Engineering & Applied Science Journal, 2026)
In recent years, heavy rainfall has caused slopes to fracture in Sirimau District, resulting in landslides that have yet to be addressed by the government. This is the Waehakila Hamlet, Warasia, located in Sirimau District. Complex geological conditions, high year-round rainfall, and increasingly dense residential activity on the slopes make this area highly vulnerable to land instability. Soil research uses the SNI method for property testing, to determine soil characteristics using the USCS and AASTHO methods, while to determine slope stability using the Fellenius and Bishop methods. Based on the results of the tests and data analysis carried out, it was concluded that the slope was in a stable condition with a safety factor using the Fellenius method F = 4.93 ok >1.5 and the Bishop method F = 4.93 ok >1.5 according to the location conditions and soil characteristics and was classified as a mixed slope type. Keywords: Soil, Slope stability, Fellenius.